Modification of the pore structures of fuel cell electrodes using a dry etching technique - Kim, Woon-Jo; Mehmood, Asad; Lee, Kwan-Young; Ha, Heung Yong (ELSEVIER SCIENCE BV, 2013)
The anodes of membrane-electrode assemblies (MEAs) have been treated with an argon ion-beam under vacuum to etch out a part of the ionomer present in the catalyst layers. The ion beam treatment alters the surface morphology of the catalyst layer by promoting the pore size and overall porosity, which reduces the mass transport resistance of the reactants and the products through the catalyst layers. As confirmed, the electrochemical surface areas of the electrodes are not affected by the treatment, and the ion-beam-treated MEAs exhibit improved performance toward direct methanol fuel cells (DMFCs). Physical and electrochemical analyses have been carried out to characterize the modified electrodes in greater detail. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CATALYST LAYER; PERFORMANCE; MEMBRANE; SURFACE; MICROSTRUCTURE; SOLVENT; INK